Investigation of the enantiomerization barriers of the phthalimidone derivatives EM12 and lenalidomide by dynamic electrokinetic chromatography - Walz, Sarah; Weis, Sylvia; Franz, Mareike; Rominger, Frank; Trapp, Oliver (Electrophoresis, 2015)
The phthalimidone derivatives EM12 and lenalidomide, which are both structurally related to thalidomide, are highly interesting drugs and very recently lenalidomide attracted great attention as an antitumor and immune-modulating drug [1] in the therapy for multiple myeloma [2]. EM12 and lenalidomide are chiral, and the stereogenic carbon C-3 in the piperidine-2,6-dione moiety of these phthalimidone derivatives is prone to interconversion due to keto-enol tautomerization. The knowledge of the enantiomerization barrier [3-47] is mandatory for pharmacokinetic studies and to develop a tailored therapy using the enantiopure or racemic drug. Here, we used dynamic EKC in combination with direct-calculation methods to determine the enantiomerization barriers of EM12 and lenalidomide. The separations of the enantiomers of EM12 and lenalidomide were performed in 50 mM aqueous disodium hydrogen phosphate buffer at pH 8 and 50 mM aqueous sodium tetraborate buffer at pH 9.3, respectively, using 20 mg/mL heptakis-(2,3-diacetyl-6-sulfato)-β-CD as a chiral additive. Enantiomerization of the compounds during the electrokinetic chromatographic separation resulted in pronounced plateau formation between the well-separated enantiomers. Peak form analysis of the experimentally obtained interconversion profiles yielded the enantiomerization rate constants k1 of EM12 and lenalidomide as well as the kinetic activation parameters ΔG‡, ΔH‡‡, and ΔS‡ of enantiomerization by the evaluation of temperature-dependent measurements. The enantiomerization barrier ΔG‡ was determined to be 98.3 ± 1.0 kJ/mol; the activation parameters ΔH‡ = 46.1 ± 2.4 kJ/mol and ΔS‡ = −170 ± 61 J/(K·mol) for EM12 and ΔG‡ = 91.5 ± 1.0 kJ/mol, ΔH‡ = 62.4 ± 5.4 kJ/mol, and ΔS‡ = −98 ± 7 J/(K·mol) for lenalidomide. These findings were corroborated by density functional theory calculations at the B3LYP/3-21G level of theory of the ground state and intermediates considering an enantiomerization pathway via a keto-enol tautomerism.
First published: 11 December 2014
Gesehen am 29.06.2020